The Development and Implementation of an Autopsy/ Tissue Donation for Breast Cancer Research. Issue 4 (2nd October 2021) - Rosenzweig, Margaret; Miller, Lori A.; Lee, Adrian V.; Oesterreich, Steffi; Trejo Bittar, Humberto E.; Atkinson, Jennifer M.; Welsh, Ann
Abstract : There is growing interest in tissue procurement for cancer research through autopsy. Establishing an autopsy/tissue donation programme for breast cancer research within an academic medical centre in the United States requires consideration, planning, multi-departmental collaboration and labour-intensive maintenance. It is the purpose of this paper to outline the necessary considerations in implementing and maintaining a tissue donation and autopsy programme within a breast cancer centre at a comprehensive cancer centre. Considerations of programme planning include: patient engagement, the recruitment of patients and families into the programme, the role and scope of work of the clinical coordinator, regulatory issues and the coordination with both pathology and the research team at time of death and autopsy/tissue donation. All aspects of the tissue donation/rapid autopsy programme development and implementation are discussed and illustrated through case study. An Autopsy/ Tissue Donation for breast cancer research can be successfully developed and implemented.